Activation of the C-Type Lectin MGL by Terminal GalNAc Ligands Reduces the Glycolytic Activity of Human Dendritic Cells - Zaal, Anouk; Li, R. J. Eveline; Lübbers, Joyce; Bruijns, Sven C. M.; Kalay, Hakan; van Kooyk, Yvette; van Vliet, Sandra J. (Frontiers in Immunology, 2020)
Many tumors display alterations in the biosynthetic pathways of glycosylation, resulting in increased expression of specific tumor-associated glycan structures. Expression of these altered glycan structures is associated with metastasis and poor prognosis. Antigen presenting cells can recognize tumor-associated glycan structures, including the truncated O-glycan Tn antigen, via specific glycan receptors. Tn antigen-mediated activation of the C-type lectin MGL on dendritic cells induces regulatory T cells via the enhanced secretion of IL-10. Although these findings indicate that MGL engagement by glycan ligands can modulate immune responses, the impact of MGL ligation on dendritic cells is still not completely understood. Therefore, we employed RNA sequencing, GO term enrichment and pathway analysis on human monocyte-derived dendritic cells stimulated with two different MGL glycan ligands. Our analyses revealed a reduced expression of genes coding for key enzymes involved in the glycolysis pathway, TCA cycle and oxidative phosphorylation. In concordance with this, extracellular flux analysis confirmed the decrease in glycolytic activity upon MGL triggering in human dendritic cells. To our knowledge, we are the first to report a diminished glycolytic activity of human dendritic cells upon C-type lectin stimulation. Overall, our findings highlight the impact of tumor-associated glycans on dendritic cell biology and metabolism and will increase our understanding on how glycans can shape immunity.